2009
DOI: 10.1007/s12011-009-8546-z
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Arsenic Levels in Women with Different Body Mass Composition

Abstract: The objective of this study was to evaluate whether lead (Pb) and arsenic (As) levels in biological fluids were associated to the body composition in a group of reproductive-age women. Voluntary childbearing-age women (n=107) were divided into three groups according to their body mass index (BMI: weight/height 2 (kg/m 2 ): low weight (BMI<18.5 kg/m 2 ), normal BMI > 19 < 24:9 kg m 2 À Á , and overweight (BMI>25 kg/m 2 ). Body composition and fat mass percentage were determined by the isotopic dilution method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
19
1
3
Order By: Relevance
“…In another study, Ronco and colleagues also found no significant correlation between blood lead level and both BMI and body fat percentage. In addition, this study also could not reveal the role of BMI or body composition in the regulation of lead toxicity (Ronco et al 2010). Our finding, however, was in contrast with a previous study by Rustanti and Mahawati involving public transportation drivers where a significant negative correlation was indicated between blood lead level and BMI (r=-0.38; p<0.05) (Rustanti & Mahawati 2011).…”
Section: Resultscontrasting
confidence: 99%
“…In another study, Ronco and colleagues also found no significant correlation between blood lead level and both BMI and body fat percentage. In addition, this study also could not reveal the role of BMI or body composition in the regulation of lead toxicity (Ronco et al 2010). Our finding, however, was in contrast with a previous study by Rustanti and Mahawati involving public transportation drivers where a significant negative correlation was indicated between blood lead level and BMI (r=-0.38; p<0.05) (Rustanti & Mahawati 2011).…”
Section: Resultscontrasting
confidence: 99%
“…Human studies show conflicting evidence with Pb measured in teeth positively correlating with BMI at age 7, while Pb levels in patella and tibia of children the same age did not correlate with BMI, and cross-sectional studies of blood lead level found no association with obesity in 11 year old children or adult women [10], [38][40]. In contrast, Pb had a negative association with BMI and waist circumference in the NHANES 1999–2000 cohort [11].…”
Section: Discussionmentioning
confidence: 94%
“…Whereas Both Miguel A. Padilla et al and Franco Scinicariello et al reported that BLL associated with lower body weight in adults based on data from NHANES [1, 21]. In another study, no association was found between BLL and BMI in adults [22]. The conflicting results may be due to ethnic variations as well as different BLL of the study population.…”
Section: Discussionmentioning
confidence: 97%